(untitled) (Rudarsko-geološko-naftni zbornik, 2020)
Area development deals with optimal land use and the reduction of the risk of geological disasters. The coastal area of South Bali is prone to land settlement hazards. In order to mitigate the risk, it is important to understand the depositional environment of the area related to its bearing capacity and geological hazard risks. The aim of this research is to understand the subsurface depositional environment and quantifying its bearing capacity. Quantitative modeling was carried out to obtain the sediment-bearing capacity of the Pendungan area in Bali, Indonesia. The methods used in this research were the observation of borehole cores, the identification of the cone penetration test (CPTu) curves pattern, the sediment index property test, the soil strength laboratory, and bearing capacity analysis. Based on lithologic association, the CPTu curve pattern, and grain size analysis, there are three facies developing in the study area with different bearing capacity values. Generally, beach ridge sand has a higher bearing capacity (N-SPT value of 8 – 52) for shallow foundation than fluvial clay. Meanwhile, floodplain facies has the lowest bearing capacity (N-SPT value of 2 – 20).